Pengaruh Hubungan Antara Government E-Readiness dan Citizen E-Readiness Dengan Kepatuhan Wajib Pajak - Rossi Adi Nugroho; Cris Kuntadi (Universitas Sains dan Teknologi Komputer, 2023)
The level of tax compliance has been a concern of researchers and governments for decades. Various efforts have been made by the government in order to increase taxpayer compliance including the use of information and communication technology in service delivery (e-government) but have not yielded optimal results. Various studies and research related to taxpayer compliance and its relationship with e-government have also been carried out but are still focused on e-government services regardless of the level of readiness (e-readiness) of the government itself as a service provider (government e-readiness) or from the community side as service users (citizen e-readiness). Writing this article aims to build a new hypothesis with the variable level of readiness (e-readiness) as a variable that affects government services which will ultimately increase the level of taxpayer compliance. Previous research or relevant research is used to strengthen the theory and phenomenon of the relationship or influence between variables.